A bibliometric analysis on mobile government research. (23rd February 2022) - Hebbar, Sunith; Kiran, K.B.
Mobile government (MG) being a critical subset of e-government system has gained a lot of prominence among the practitioners and researchers. With its complex nature, MG has not achieved the desired success rate, and has therefore led to numerous research studies. Thus, with the diverse literatures on MG, it is critical to take stock of the existing literature and systematically categorise all documents. This will assist the aspiring researchers in understanding the topic, categorising and systematically deriving the objectives for their study. Thus, this study performs a bibliometric analysis (co-citation analysis and bibliometric coupling analysis) using Scopus database on MG research. The resulting clusters from these analyses are then used to identify the seminal works, themes in MG research and to determine research gaps for directing future studies. Overall, this study gives clear picture of MG research and also directs future research that contributes significantly to the field.